A NEW ACT OF ROGER, ARCHBISHOP OF YORK, 1154-1181: FURTHER EVIDENCE OF FORGERY AT NOSTELL PRIORY? - Carpenter, David X. (Northern History, 2014)
A previously unnoticed act of Archbishop Roger confirms an agreement between Henry de Lacy, lord of the honour of Pontefract, and the Augustinian priory of Nostell. It casts new light on the dispute in the 1150s between Henry and the priory. Their disagreement concerned the gifts that had been made to Nostell by Hugh de Laval, who had held the honour of Pontefract c. 1110 to c. 1129 after the forfeiture of Robert de Lacy, Henry’s father. There was a similar dispute with Pontefract Priory, which the monks attempted to resolve by forgery. The new act is at odds with other evidence, and the suggestion is made that the canons of Nostell, too, were resorting to forgery in their dispute with the Lacy family.